Violence assessment and intervention the practitioner's handbook - Cawood, James S. (CRC Press, 2009)
Offers a methodology for analyzing potential threat situations and taking action before tragedy occurs. Demonstrating the violence risk assessment model from the point of the initial call, this handbook covers information gathering, victimology, and formulas and tools for risk assessment. It explores organizational influences and ethics.